RECYCLING OF SCRAP AND WASTE OF COPPER AND COPPER ALLOYS IN BELARUS - S. L. Rovin; L. M. Novak; A. V. Fateev (Литьë и металлургия)
The construction of a new casting and mechanical shop of unitary enterprise «Tsvetmet» in December 2015 has allowed to solve the complex problem of processing and utilization of scrap and wastes of copper and copper alloys in the Republic of Belarus. The technological processes of fire refinement of copper and manufacturing of copper rod from scrap and production of brass rod by hot pressing (extrusion) of the continuously casted round billet have been mastered for the first time in the Republic of Belarus.